Posyandu Cadres' Contributions to Elderly Health Improvement - Isnanik, Isnanik; Rodiyah, Isnaini (Indonesian Journal of Cultural and Community Development, 2024)
Background: This study investigates the role of community health workers in promoting elderly health through integrated health posts. Specific Background: A qualitative descriptive approach is used to examine the significance of these workers in ensuring regular attendance of the elderly at health services. Knowledge Gap: While previous studies have focused on health post activities, they often overlook the specific strategies employed by community health workers. Aims: The study aims to clarify the contributions of community health workers in facilitating elderly health programs. Results: Findings indicate that these workers adapt activities, such as health consultations and educational sessions, to enhance elderly participation and health outcomes. Novelty: The research provides new insights into innovative service delivery by community health workers amid logistical challenges. Implications: The results highlight the need for ongoing support and training for community health workers, advocating for structured programs to enhance elderly engagement and well-being, with potential applications in similar contexts to improve elderly healthcare. Highlights : Community health workers play a crucial role in facilitating elderly health services. Adaptation of activities enhances elderly engagement and health outcomes. Continuous support and training for health workers are essential for effective program implementation. Keywords: community health workers, elderly health, qualitative study, health post, participation